Dinámica y predicción de la interacción entre los receptores de membrana presentes en monocitos (DC-SIGN, CLEC5A y MR) y proteínas de la envoltura de la familia Flaviviridae (2020)
Protein-protein interaction is fundamental to many biological processes. For example, viruses can enter the cells of their host thanks to the interaction with receptors present in cells of the immune system, which are mostly protein types. One of the methods used to know how the interaction between proteins occurs is molecular docking, however methods that are based on the information of sequestration can also be useful to know the possible interaction between proteins. Therefore, in this study these two methods are used to know how the interaction between envelope proteins of viruses belonging to the flaviviridae family occurs for three receptors present in monocytes.